К ВОПРОСУ МОНИТОРИНГА СОСТОЯНИЯ И ФУНКЦИОНИРОВАНИЯ БИОТЫ ЮЖНОГО ПРИАРАЛЬЯ - Таумуратова, Г.Н. (SCIENCE and SOCIETY, 2025)
The article discusses the issues of monitoring the functioning of the biota of the Southern Aral Sea region in modern conditions. It is shown that indicators of change are indicators that characterize not only individual components of nature, but also complexes as a whole. Carrying out environmental regulation of anthropogenic impacts on biota serves as the basis for recommendations in the field of environmental protection.
Keywords: biota; Aral Sea region; standardization; indicators; bioindication; ecosystems; components